2018
DOI: 10.1142/s0219519418500604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Polyacrylamide Ferrogel Elasticity on the Cell Adhesiveness to Magnetic Composite

Abstract: Biocompatible polyacrylamide gels are widely required for the development of mechanically “soft” magnetic material for the purposes of different biomedical applications. In this work, ferrogels were synthesized by radical polymerization of acrylamide in a stable aqueous suspension of magnetic maghemite [Formula: see text]-Fe[Formula: see text]O[Formula: see text] nanoparticles (MNPs) with the median value in diameter of 11.4[Formula: see text]nm fabricated by laser target evaporation. Gel network density was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…The laboratory setup for mechanical testing of gels was used as described early [ 30 , 31 ]. A cylindrical ferrogel sample (~7 mm in length and ~10 mm in diameter) placed in a bath filled with Hanks’ solution was clamped vertically between two parallel plates connected to the levers of the force transducer and the linear motor equipped with an optical transducer for the gel length measurement.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The laboratory setup for mechanical testing of gels was used as described early [ 30 , 31 ]. A cylindrical ferrogel sample (~7 mm in length and ~10 mm in diameter) placed in a bath filled with Hanks’ solution was clamped vertically between two parallel plates connected to the levers of the force transducer and the linear motor equipped with an optical transducer for the gel length measurement.…”
Section: Methodsmentioning
confidence: 99%
“…The possibility of ferrogel usage for cellular scaffolds has been reported in a number of studies [ 27 , 28 , 29 ]. For instance, in our early works, we demonstrated a good compatibility of cells with polyacrylamide-based ferrogels [ 30 , 31 ]. In particular, it was found that the adhesive activity of human dermal fibroblasts become larger with the increase of MNPs concentration in the composite, so that at the 1.0% weight fraction of MNPs in ferrogel, the cell adhesion appeared to be comparable to the cultural plastic widely used in cellular technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elastic properties of the gels were evaluated by mechanical testing of the samples as described elsewhere [6,8,10]. Briefly, stepped strains for compression of up to 20% of the initial length were set to samples of gels while using a linear motor with a step of 1–2%.…”
Section: Methodsmentioning
confidence: 99%
“…Different studies had established the fact that the elastic properties of PAA ferrogels can significantly vary, depending on the details of synthesis conditions, as well as change their mechanical characteristics in response to an external magnetic field [4,7,8]. It is also known that polyacrylamide ferrogels have low toxicity and good compatibility to living cells [9,10]. Based on this advantage, PAA ferrogels have been used as substrates (scaffolds) for cell culturing for the needs of cellular technologies and tissue engineering [11].…”
Section: Introductionmentioning
confidence: 99%